2015
DOI: 10.1073/pnas.1418139112
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 is a critical mediator in Ataxia telangiectasia disease

Abstract: Ataxia telangiectasia (A-T), a rare autosomal recessive disorder characterized by progressive cerebellar degeneration and a greatly increased incidence of cancer among other symptoms, is caused by a defective or missing ataxia telangiectasia mutated (ATM) gene. The ATM protein has roles in DNA repair and in the regulation of reactive oxygen species (ROS). Here, we provide, to our knowledge, the first evidence that NADPH oxidase 4 (NOX4) is involved in manifesting A-T disease. We showed that NOX4 expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
3
27
1
Order By: Relevance
“…Furthermore, recent studies have indicated alternative, endogenous sources of oxidative stress in A-T, BS and NBS cells including NADPH oxidase 4 (NOX4), oxidised low-density lipoprotein (ox-LDL) or Poly (ADP-ribose) polymerases (PARP-1, PARP-2, PARP-3) (Fig. 2) [47], [48], [59], [65] which may provide new pharmacological strategies for patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, recent studies have indicated alternative, endogenous sources of oxidative stress in A-T, BS and NBS cells including NADPH oxidase 4 (NOX4), oxidised low-density lipoprotein (ox-LDL) or Poly (ADP-ribose) polymerases (PARP-1, PARP-2, PARP-3) (Fig. 2) [47], [48], [59], [65] which may provide new pharmacological strategies for patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the authors evaluated a relationship between ATM deficiency, oxidative DNA damage, neurodegeneration and cancer susceptibility in A-T disease. They demonstrated that NOX4, which constitutively produces ROS in a gamut of cell types and tissues as well as plays a crucial role in oxidative DNA damage and the subsequent senescence [49], was highly up-regulated in A-T patients, similarly to normal cells with a lack of ATM protein kinase [48]. Additionally, NOX4 correlated with higher oxidative damage and apoptosis.…”
Section: Ataxia-telangiectasia Atm Protein Kinase and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…This antioxidant dramatically delayed the onset of thymic lymphomas in Atm-deficient mice and corrected the neurobehavioral defects (Gueven et al, 2006), indicating that oxidative stress is an important contributor to the neurodegenerative and cancer-prone phenotype of A-T. The expression of NADPH oxidase (Nox4), a ROS-generating enzyme, was recently shown to be increased in A-T cells and sections of cerebellum from A-T patients (Weyemi et al, 2015). Elevated oxidative stress is also evident in cultured astrocytes from Atmdeficient mice (Liu et al, 2005;Kim and Wong 2009).…”
Section: Ratmentioning
confidence: 99%